Progressive tool-wear in machining of room-temperature austenitic NiTi alloys: The influence of cooling/lubricating, melting, and heat treatment conditions - KAYNAK, YUSUF (ELSEVIER SCIENCE SA, 2015)
This study investigates the effects of fabrication (vacuum arc remelting (VAR) melted vs. vacuum induction melting combined with VAR (VIM + VAR)), processing (hot rolled + fully annealed vs. cold worked + superelastic anneal) and machining conditions (dry, cryogenic, and minimum quantity lubrication (MQL)) of NiTi alloys on their progressive tool-wear behavior. Experimental findings reveal that cryogenic machining substantially improves the performance of cutting tools by reducing the progressive tool-wear in machining of the room-temperature austenitic NiTi alloys. Therefore, cryogenic machining could result in improved productivity and reduced manufacturing costs compared to dry and MQL machining. Experimental evidence suggests that cold working did not alter the progressive tool-wear substantially; however, the presence of carbide inclusions increased the progressive tool-wear in machining NiTi. Surface quality of machined samples under cryogenic machining presents promising improvement upon short-duration machining compared to dry and MQL machining, but all three techniques resulted in comparable quality after 4 min of machining. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Machining; Tool-wear; Room-temperature austenitic NiTi alloys; Cooling/lubricating; Melting; Heat treatment; SHAPE-MEMORY ALLOYS; MEDICAL APPLICATIONS; SURFACE INTEGRITY; PERFORMANCE; MQL; DRY; ROUGHNESS; ACCURACY